CURRENT CHALLENGES IN ENVIRONMENTAL EDUCATION: CASE STUDY OF HUMAN-INDUCED LANDSCAPES DYNAMICS - Tamara Dudar; Tetiana Saienko; Iryna Matvieieva; Valentyna Groza; Tetiana Karpenko; Anna Kozlova; Margaryta Radomska; Volodymyr Savytskyi; Andrian Yavniuk (Environmental Problems, 2022)
The purpose of the article is to present the research results on the landscape changes dynamics in the frame of the Educational and Professional Program “Ecology and Environmental Protection” developed at the Department of Environmental Sciences at National Aviation University. The noosphere paradigm as the most integral bio-adequate basis of the interaction between the society and ambient environment under conditions of present-day challenges is highlighted. The advantages of education in English are emphasized in terms of the abundance of primary educational sources to tackle environmental challenges especially connected with the warfare activities in the country. Digital technologies and remote sensing development within the framework of the educational and professional program provide students, in particular, with the opportunity to perform landscape changes assessment due to long-term anthropogenic stress. The example of the border region landscapes of the Novgorod-Siverskyi Polissia is considered.